Assessment of the effects of lubricants on condoms - จงธรรมวัฒน์, สุภาวรรณ; กล่อมแก้ว, สถาพร; ดวงสว่าง, วันเพ็ญ (Disease Control Journal, 2014)
The objective of this study was to investigate the effects of added lubricants on latex condoms by determining bursting pressure and bursting volume in accordance with the Thai Industry Standard, TIS 625 B.E.2554. The materials used in the study included 700 pieces of natural latex rubber condoms procured from a domestic manufacturer; and 2 types of lubricants: water-based (lubricating jelly) and oil-based (baby oil, body lotion, petroleum jelly, vegetable oil). An air inflation tester was used to examine the bursting pressure and the bursting volume of 32 pieces of the samples after adding a lubricant for the periods of 5, 10, 30 and 45 minutes. The procedure was repeated for all 5 lubricants; and the bursting pressure and the bursting volume of condoms without adding lubricants were used as control. It was found that the average bursting pressure and bursting volume of condoms treated by adding water-based lubricant were similar to those of the control group. No deterioration was found in all periods. However, the average bursting pressure and bursting volume of condoms treated by added oil-based lubricant were found to be lower than those of the control group. Based on the results, the authors recommended that condom users should not apply any oil-based lubricant on the condoms in order to avoid condom deterioration.